Flight capital and its reversal for development financing - Niels Hermes; Robert Lensink; Victor Murinde (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2002)
In this paper, we review the theoretical and empirical literature on capital flight. First, we discuss the measurement of capital flight. Next, we provide information on the magnitude as well as the `burden' of capital flight for a selected set of developing countries in four regions of the world (South Asia, East Asia, Sub-Saharan Africa and Latin America). Moreover, we review the literature on the determinants of capital flight and provide an overview of empirical studies that have analysed the determinants of capital flight. In the light of the discussion of these determinants, we assess the prospects for flight capital reversal. We conclude by proposing some policy measures to stem continued capital flight and induce capital flight reversal.
Keywords: F29; F39; O11; 330; capital flight; flight capital reversal; development finance; Kapitalflucht; Entwicklungsfinanzierung; Entwicklungsländer; Südasien; Ostasien; Zentralafrika; Lateinamerika